Ultrasound‐Mediated Diagnosis and Therapy based on Ultrasound Contrast Agents. Issue 8 (17th July 2017) - Yoon, Young Il; Tang, Wei; Chen, Xiaoyuan
Abstract : Ultrasound‐mediated diagnosis techniques have consistently attracted worldwide attention. Compared with other medical‐diagnosis methods, relatively distinguished features of ultrasound being readily accessible, swift, inexpensive, and safe make it routinely used for diverse purposes. With the development of ultrasound‐imaging devices, the recent advent of ultrasound contrast agents (UCAs) has expanded the sphere of ultrasound's influence to therapy. UCAs, which are generally gas‐filled and microsized bubbles, have been grafted onto multifunctional particles or molecules to selectively detect various diseases and effectively treat them. Additionally, nanosized bubbles as well as microsized bubbles have lately received a lot of attention since the phase‐transition behavior of the bubbles is observed under certain conditions. The focus here is an introduction to and the preparation of therapeutic and multimodal UCAs. Also, high‐intensity focused ultrasound (HIFU), among the ultrasound‐mediated techniques, which enables researchers and health‐care providers to overcome existing approaches, is described in depth. To close, the future and challenges of diagnosis and therapy with ultrasound are reviewed. Abstract : Multifunctional ultrasound contrast agents (UCAs) can overcome the limitations of existing UCAs and treat various diseases. With the rising interest in image‐guided therapy, therapeutic‐content‐containing UCAs are selected as a new paradigm. Moreover, the development of multimodal imaging contrast agents allows various diseases to be detected by using ultrasound imaging together with optical, magnetic resonance, computed tomography, single‐photon‐emission computed tomography, and photoacoustic imaging.